Hubungan Antara Motivasi Kerja Dengan Disiplin Kerja Perawat Di Ruang Rawat Inap Rumah Sakit Jogja - Agus Sarwo Prayogi (JURNAL WACANA KESEHATAN, 2016)
1Agus Sarwo Prayogi, 2 Sri Rizki Andani, 3 Kirnantorosaworbali@gmail.com Abstract The increased attitude of discipline is very important for the growth of the organization used primarily to motivate employees to be able to discipline themselves in carrying out the work of both individuals and groups. Labor discipline can be seen from the level of attendance and punctuality came to office. Knowing the relationship between work motivation and work discipline of nurses in the inpatient hospital of Yogyakarta. The research method uses observational with cross sectional approach. The research subjects are nurses in the inpatient hospital Jogja with a sample of 87 respondents, the sampling technique nonprobability sampling by purposive sampling. The results obtained the majority of nurses work motivation levels in a category are 50 respondents (57.5%) and the level of discipline of nurses in the inpatient hospital Jogja majority are in good category were 68 respondents (78.2%) , Analysis of test results obtained the value of correlation coefficient between work motivation and discipline of nurses at 0.342 with P = 0,002 (p < 0,05), which means that H0 rejected and Ha accepted. Conclusion: There was a significant correlation between work motivation and discipline of nurses in the inpatient hospital of Yogyakarta. Keywords: work motivation, work discipline nurses, hospital 1,3 Jurusan Keperawatan Poltekes Kemenkes Yogyakarta2    Prodi Ilmu Keperawatan STIKes Surya Global Yogyakarta